Faktor Risiko Stunting pada 1000 Hari Pertama Kehidupan: Faktor Risiko Stunting pada Seribu Hari Pertama Kehidupan - Indri Mulyasari; Asti Jatiningrum; Arum Putri Setyani; Raden Roro Susanti Septi Kurnia (Universitas Airlangga, 2022)
Background: Kebonaagung is one of focus locations of stunting in Semarang Regency. Stunting affected by risk factors that exist in the first thousand days of life. Objectives: To examine the increased risk of stunting in toddlers based on maternal mid upper arm circumference (MUAC) in early pregnancy, maternal anemia status in third semester, birth weight, and birth length. Methods: This research design was analytic observational with cohort retrospective approach. Population was toddlers aged 12-35 months in Kebonagung Sumowono District Semarang Regency. There were 71 subjects in this research obtained by total sampling technique. MUAC, anemia status, birth weight, and birth length data were obtained by the subjects maternal and child health book. Data of stunting was taken by doing nutritional anthropometry assessment procedures. Data analysis was done by counting relative risk (RR). Results: There are 25.35% toddlers with stunting, 25.35% mothers of the toddlers with history of risk of chronic energy deficiency, 25.35% mothers of the toddlers experiencing anemia in third semester of pregnancy, 14.08% toddlers have history low birth weight, and 16.90% of toddlers have history of short birth length. Small MUAC size in early pregnancy, low hemoglobin level in the third semester of pregnancy, low birth weight, and short birth length are increasing risk of becoming stunting in toddlers (RR = 1.87 (95% CI: 0.86-4.09); RR = 1.47 (95% CI: 0.65-3.35); RR = 1.22 (95% CI: 0.36-4.37); RR = 1.41 (95% CI: 0.56-3.53), respectively). Conclusions: Nutritional status of pregnant women and infant can affect stunting incidence in toddlers. Stunting prevention program in the first thousand days of life period is need to be done.